School curricula, educational trajectories, and labor market outcomes - Benjamin W. Arold (ifo Institut - Leibniz-Institut für Wirtschaftsforschung an der Universität München, 2022)
Benjamin W. Arold prepared this study while he was working at the Center for Economics of Education at the ifo Institute. The study was completed in March 2022 and accepted as doctoral thesis by the Department of Economics at the LMU Munich. It consists of four distinct empirical essays that address various aspects of how school curricula affect students in the classroom and beyond. Chapter 2 demonstrates that the abolishment of compulsory religious education in Germany does not only affect religiosity and gender role attitudes, but also affects the high-stakes choices of getting married, having children and participating in the labor market. Chapter 3 provides evidence that the content of science education standards in the US does not only affect related knowledge of students and adulthood attitudes, but also translates into high-stakes occupational choices. Chapter 4 exemplifies that school curricula reforms can also have unintended consequences by showing that a reform of education standards in math and English has negative spillovers on student achievement in science. Finally, Chapter 5 highlights the fundamental role teachers, the transmitters of educational content in school, play in the formation of human capital even in dimensions generally thought of as genetically determined.
Keywords: I21; I24; I28; I29; J24; H75; P16; Z12; 330; Religious Education; Religiosity; School Reforms; Evolution; Religion; Science Education; Education Standards; Human Capital; Attitudes; Beliefs; Occupational Choice; Common Core; Education Standards; StudentAchievement; Education Policy; Polygenic Scores; School Resources; SkillFormation